A The Role of Self Control as a Moderating Variable on The Effect of Financial Inclusion on Financial Behavior - Ardiana, Meta; Agustina, Rachma; Pertiwi, Dwi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
Financial behavior among the public is still low, based on research conducted by the OCBC Financial Index showing data that the financial literacy and behavior index of the younger generation is still in the low range category, namely 37.72 out of 100 in 2021 for 1,027 respondents. Previous research on